Improved diffusion tensor imaging of the optic nerve using multishot two‐dimensional navigated acquisitions. Issue 4 (26th September 2014) - Jeong, Ha‐Kyu; Dewey, Blake E.; Hirtle, Jane A.T.; Lavin, Patrick; Sriram, Subramaniam; Pawate, Siddharama; Gore, John C.; Anderson, Adam W.; Kang, Hakmook; Smith, Seth A.
<x xml:space="preserve">Abstract</x> Purpose A diffusion‐weighted multishot echo‐planar imaging approach combined with SENSE and a two‐dimensional (2D) navigated motion correction was investigated as an alternative to conventional single‐shot counterpart to obtain optic nerve images at higher spatial resolution with reduced artifacts. Methods Fifteen healthy subjects were enrolled in the study. Six of these subjects underwent a repeated acquisition at least 2 weeks after the initial scan session to address reproducibility. Both single‐shot and multishot diffusion tensor imaging studies of the human optic nerve were performed with matched scan time. Effect of subject motions were corrected using 2D phase navigator during multishot image reconstruction. Tensor‐derived indices from proposed multishot were compared against conventional single‐shot approach. Image resolution difference, right–left optic nerve asymmetry, and test–retest reproducibility were also assessed. Results In vivo results of acquired multishot images and quantitative maps of diffusion properties of the optic nerve showed significantly reduced image artifacts (e.g., distortions and blurring), and the derived diffusion indices were comparable to those from other studies. Single‐shot scans presented larger variability between right and left optic nerves than multishot scans. Multishot scans also presented smaller variations across scans at different time points when compared with single‐shot counterparts. Conclusion The multishot technique has considerable potential for providing improved information on optic nerve pathology and may also be translated to higher fields. Magn Reson Med 74:953–963, 2015. © 2014 Wiley Periodicals, Inc.